Preliminary exploration of bioactive compounds and anthelmintic activity in diospyros kaki Fruits - Anandarajagopal Kalusalingam; Aineesha Hani Johari Rozario; Poonguzhali Subramanian; Abdullah Khan; Senthilraj Rajapandi; Saravana Muthu Kumar Pandian; Punniyakoti V Thanikachalam; Ming, Long Chiau; Asmuni Mohd Ikmal (Penerbit Universiti Kebangsaan Malaysia, 2024)
Helminths, or parasitic worms, pose a significant global health concern, affecting more than 25% of the world's population. In Malaysia, these infections are endemic, with varying prevalence rates among different populations, especially those impacting economically disadvantaged communities. The present study aimed to determine the secondary metabolites present and evaluate the anthelmintic activity of Diospyros kaki fruit extracts against earthworms. Hexane, ethyl acetate, ethanol, and water extracts of Diospyros kaki fruits were obtained via the cold maceration technique. Preliminary phytoconstituent screening of Diospyros kaki fruit extracts was performed to identify the phytoconstituents present in the extracts. The anthelminthic activities of different extracts (200 and 300 mg/mL) of Diospyros kaki fruits were evaluated separately in adult Malaysian earthworms (Pheretima posthuma). The durations of paralysis and death of individual worms were determined and compared with those of the standard drug albendazole at a concentration of 40 mg/mL. Ethyl acetate extract of D. kaki fruits at a concentration of 300 mg/mL resulted in better anthelmintic activity than the standard drug, albendazole, and other D. kaki fruit extracts. Qualitative phytochemical analysis revealed the presence of tannins, flavonoids, alkaloids, and volatile oils that might contribute to the anthelmintic activity of D. kaki fruits. Further research is intended to isolate anthelmintic bioactive compounds that could serve as new lead structures for developing alternative novel herbal anthelmintic agents.